THE USE OF ANIMATED LEARNING VIDEO IN TEACHING VOCABULARY IN PROCEDURE TEXT - Rahmaniar, Salwani; Regina, Regina; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research investigated whether or not using animated learning video as teaching media was effective in teaching vocabulary. This was a pre-experimental research with one group pre-test and post-test design. The population was the seventh grade students of SMPN 1 Sungai Ambawang and the sample was the VII A which consists of 17 students. The data were collected using objective tests and analyzed by t-test and effect size formula. The obtained t-value (12.57) was bigger than the critical value of r (1.746) by the degree of freedom 16 meaning that animated learning video increased the studentsâ€™ vocabulary. The effect size was categorized as high effect since the ES value (2.76)was bigger than the reliability coefficient of the test (0.8). So, based on the research findings, the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) which states that â€œTeaching vocabulary by using animated learning video is significantly effectiveâ€ was accepted. To conclude, the use of animated learning video is highly significantly effective to teach vocabulary to the seventh grade students of SMPN 1 Sungai Ambawang in Academic Year 2017/2018.Â Keywords: Animated Learning Video, Vocabulary, Teaching Media